Interactions between N‐linked glycosylation and polymerisation of neuroserpin within the endoplasmic reticulum. (3rd October 2015) - Moriconi, Claudia; Ordoñez, Adriana; Lupo, Giuseppe; Gooptu, Bibek; Irving, James A.; Noto, Rosina; Martorana, Vincenzo; Manno, Mauro; Timpano, Valentina; Guadagno, Noemi A.; Dalton, Lucy; Marciniak, Stefan J.; et al.
Abstract : The neuronal serpin neuroserpin undergoes polymerisation as a consequence of point mutations that alter its conformational stability, leading to a neurodegenerative dementia called familial encephalopathy with neuroserpin inclusion bodies (FENIB). Neuroserpin is a glycoprotein with predicted glycosylation sites at asparagines 157, 321 and 401. We used site‐directed mutagenesis, transient transfection, western blot, metabolic labelling and ELISA to probe the relationship between glycosylation, folding, polymerisation and degradation of neuroserpin in validated cell models of health and disease. Our data show that glycosylation at N157 and N321 plays an important role in maintaining the monomeric state of neuroserpin, and we propose this is the result of steric hindrance or effects on local conformational dynamics that can contribute to polymerisation. Asparagine residue 401 is not glycosylated in wild type neuroserpin and in several polymerogenic variants that cause FENIB, but partial glycosylation was observed in the G392E mutant of neuroserpin that causes severe, early‐onset dementia. Our findings indicate that N401 glycosylation reports lability of the C‐terminal end of neuroserpin in its native state. This C‐terminal lability is not required for neuroserpin polymerisation in the endoplasmic reticulum, but the additional glycan facilitates degradation of the mutant protein during proteasomal impairment. In summary, our results indicate how normal and variant‐specific N‐linked glycosylation events relate to intracellular folding, misfolding, degradation and polymerisation of neuroserpin. Abstract : Neuroserpin is a protease inhibitor secreted by neurons. Point mutations promote its polymerisation, causing the neurodegenerative dementia FENIB. Neuroserpin has three predicted N‐glycosylation sites. We show that glycosylation at N157 and N321 is important for preventing polymerisation, while N401 is generally not glycosylated. Partial glycosylation of N401 in G392E neuroserpin indicates that this site reports lability of the C‐terminal end.